2017
DOI: 10.1186/s13229-017-0142-z
|View full text |Cite
|
Sign up to set email alerts
|

Replicable in vivo physiological and behavioral phenotypes of the Shank3B null mutant mouse model of autism

Abstract: BackgroundAutism spectrum disorder (ASD) is a clinically and biologically heterogeneous condition characterized by social, repetitive, and sensory behavioral abnormalities. No treatments are approved for the core diagnostic symptoms of ASD. To enable the earliest stages of therapeutic discovery and development for ASD, robust and reproducible behavioral phenotypes and biological markers are essential to establish in preclinical animal models. The goal of this study was to identify electroencephalographic (EEG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
180
4
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

7
1

Authors

Journals

citations
Cited by 144 publications
(216 citation statements)
references
References 78 publications
17
180
4
9
Order By: Relevance
“…In the TrkB Shank3B cohort, water maze was conducted last. Our previous studies with B6, BTBR, and Shank3 B had revealed similar scores in males and females on the behavioral assays used in the present studies [Yang et al, ; McFarlane et al, ; Silverman et al, , ; Kazdoba et al, ; Dhamne et al, ], therefore both males and females were approximately equally represented in the Ns for each cohort, with the exception of male–female reciprocal social interactions in which only the males were tested. Breeding were designed to yield N = 12–15 per treatment group, to provide sufficient power to detect drug effects, as confirmed in previous studies [Silverman et al, , ; Silverman, Oliver, Karras, Gastrell, & Crawley, ; Kazdoba et al, ; Stoppel et al, ].…”
Section: Methodssupporting
confidence: 63%
See 2 more Smart Citations
“…In the TrkB Shank3B cohort, water maze was conducted last. Our previous studies with B6, BTBR, and Shank3 B had revealed similar scores in males and females on the behavioral assays used in the present studies [Yang et al, ; McFarlane et al, ; Silverman et al, , ; Kazdoba et al, ; Dhamne et al, ], therefore both males and females were approximately equally represented in the Ns for each cohort, with the exception of male–female reciprocal social interactions in which only the males were tested. Breeding were designed to yield N = 12–15 per treatment group, to provide sufficient power to detect drug effects, as confirmed in previous studies [Silverman et al, , ; Silverman, Oliver, Karras, Gastrell, & Crawley, ; Kazdoba et al, ; Stoppel et al, ].…”
Section: Methodssupporting
confidence: 63%
“…Open field exploratory locomotor activity was conducted as previously described [Silverman et al, , ; Kazdoba et al, ; Dhamne et al, ]. The automated apparatus consisted of four photocell‐equipped open field chambers and VersaMax Animal Activity Monitoring System (AccuScan Instruments, Columbus, OH).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EEG was scored offline using semi-automated detection (Neuroscore, Data Sciences International, St. Paul, MN) for seizure frequency (total number of seizures), and total ictal time (cumulative time spent in seizures); where a seizure event was defined as a run of continuous spikes ≥ 3 s in duration on the EEG. Automatically detected events were verified by visual inspection (Dhamne et al 2017) Our prediction was that Torin 2 administration would lead to improvement in both parameters. We found that Torin 2 was ineffective at reducing seizure frequency in aldh5a1 −/− mice (Table 2), and unexpectedly found that it significantly extended the total ictal time (Table 2).…”
Section: Gaba and Mtor: Treatment Strategies And Pathophysiological Imentioning
confidence: 93%
“…The three‐chambered social approach was conducted as described previously . Animals were moved to the room 1 hour prior to testing.…”
Section: Methodsmentioning
confidence: 99%